Christian response amid economic suffering due to the Covid-19 pandemic - Saptorini, Sari (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2021)
The Covid-19 pandemic has caused suffering not only in the health sector but also in the economic sector. Christians are also not spared from this economic suffering. The purpose of this article is to find out how Christians should respond amid the economic suffering caused by the Covid-19 Pandemic. This research used a qualitative method and based on library research to find out the response of Christians amid economic suffering in Acts 11:27-30 and to confirm the implications for Christians today in responding to the economic suffering caused by the ongoing COVID-19 pandemic. The conclusion drawn from this study is that Christians should have faith in God who sustains their lives during the pandemic and take actions that are in line with their faith. The prosperous Christians should be willing and ready in blessing the other Christians who are suffering more. Likewise, Christians who are in economic decline respond by trusting in God's providence and humbly receiving God's blessings through the gifts of brothers and sisters who love them. Christians need to with the government in dealing with this economic suffering until the COVID-19 pandemic ends.